Rancang Bangun Smart Church Broadcasting Sebagai Upaya Penguatan Sarana Prasarana Ibadah di Masa Pandemi Covid-19 - Kristiyanto, Daniel Yeri; Safitri, Sisilia Thya (MEANS (Media Informasi Analisa dan Sistem), 2021)
The Covid-19 outbreak in Indonesia has changed the conventional worship procedures. Health protocols by the Government of Indonesia have Changed the worship of Church congregations from face to face become interface to interface through online worship. However, problems arise when Church administrators have little knowlege about the application of computer applications to Church services. This paper will explain the design of online-based worship using a smart broadcasting design using a simple V8 live soundcard, 16 channel audio mixer, OBS Studio 26.0.2, Computers, Church music equipment, handycam and social media channels. The results of this study are in the form of designing a Church worship system by utilizing the limited budget for purchasing professional broadcast equipment, but being able to digitize analog equipment owned by the Church. Futhermore, this study resulted in an equation of the application of Smart Church Broadcasting (SCB) using Fuzzy Tsukamoto.